The The Role of Sharia Digital Financial Literacy in MSME Saving and Investment Behavior - Lusiana Afrianti; Mukhlishin Mukhlishin; Nur Fitri Hidayanti (Jesya, 2026)
This study examines the role of Sharia Digital Financial Literacy in MSME saving and investment behavior in Mataram City. The growing utilization of Islamic fintech services among MSMEs highlights the need for adequate digital capability and understanding of sharia-based financial principles. However, in this study, Islamic fintech is treated as the contextual setting of financial activities rather than as a mediating variable. The research applies a quantitative approach using an explanatory survey method. A total of 110 MSME respondents were selected through purposive sampling, with the criterion of having used Islamic fintech services for at least three months. Data were collected using a Likert-scale (1–5) questionnaire measuring Sharia digital financial literacy as the independent variable, and saving and investment behavior as dependent variables. The data were analyzed using simple linear regression to assess the direct association between variables.The results indicate that Sharia Digital Financial Literacy is positively and statistically significantly associated with investment behavior. However, the explanatory power of the model is relatively low, with an R Square value of 7.1%, indicating that most of the variation in investment behavior is explained by factors outside the model. The association with saving behavior is positive but not statistically significant. These findings suggest that although Sharia digital financial literacy has a measurable statistical relationship with investment behavior, its substantive contribution remains limited. Therefore, improving MSME financial behavior likely requires consideration of additional structural, behavioral, and institutional factors beyond digital financial literacy alone.